2017
DOI: 10.1128/jcm.00150-17
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium Bacteremia: Clinical Characteristics and a Genomic Approach To Assess Pathogenicity

Abstract: Bifidobacteria are commensals that colonize the orogastrointestinal tract and rarely cause invasive human infections. However, an increasing number of bifidobacterial blood culture isolates has lately been observed in Norway. In order to investigate the pathogenicity of the Bifidobacterium species responsible for bacteremia, we studied Bifidobacterium isolates from 15 patients for whom cultures of blood obtained from 2013 to 2015 were positive. We collected clinical data and analyzed phenotypic and genotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 48 publications
1
53
0
7
Order By: Relevance
“…Bifidobacteria are ubiquitous inhabitants of the gastrointestinal tract, vagina, and mouth of mammals, including humans and are also present in guts of insects such as bees [16,17]. They have also been found in human blood, breast milk, and sewage [18][19][20]. The genomic signatures of bifidobacteria strains in different environments can give insights into how this bacterial group adapts to their environment and what types of traits are important for these adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Bifidobacteria are ubiquitous inhabitants of the gastrointestinal tract, vagina, and mouth of mammals, including humans and are also present in guts of insects such as bees [16,17]. They have also been found in human blood, breast milk, and sewage [18][19][20]. The genomic signatures of bifidobacteria strains in different environments can give insights into how this bacterial group adapts to their environment and what types of traits are important for these adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Out of more than 50 species assigned to Bifidobacterium, only 10 are found in humans. However, a previous study demonstrated the invasive potential of Bifidobacterium in immune compromised host 38 .…”
Section: Discussionmentioning
confidence: 93%
“…Ainda são controversos os resultados encontrados na literatura quanto ao uso de probióticos em pacientes imunocomprometidos. Um estudo realizado por Esaiassen et al 15 constatou bacteremia em pacientes pediátricos imunocomprometidos que utilizaram cepas de Bifidobacterium. Um estudo realizado por Wolf et al 16 com pacientes HIV positivos e imunocomprometidos mostrou que o uso de Lactobacillus reuteri foi seguro e bem tolerado pelos pacientes, não havendo nenhuma intercorrência durante o uso do probiótico, porém não houve diferença significativa na diminuição do número de evacuações diarreicas nesses pacientes.…”
Section: Discussionunclassified